Phosphorus adsorption in tropical soil, a critical review - Hanyabui, Emmanuel; Apori, Samuel, Obeng; Abindaw, Thomas; Asiamah, Joshua, Yeboah; Ali, Muhammed (My University, 2019)
In tropical soils, phosphorus adsorption is a major key process that controls its availability to crops. Phosphorus is one of the main essential plant nutrients required by the plant in large quantities. Plants absorb P either as the primary monobasic phosphate, H2PO4- ions or smaller amounts of the secondary dibasic phosphate, HPO42- ions and the phosphate ion, PO43-. Inadequate supply of phosphorus to the plant affects its potential yield nor cannot complete the reproductive cycle. Regardless of its importance to crop, it can also reduce more than 40 % of crop yield of the world’s cultivated land. Additionally, P levels in tropical soil are been depleted at a higher rate and according to some estimates from the literature reviewed there will be no P reserve in soil by the year 2050. Phosphate adsorption isotherm studies the interaction of the ions with the oxides and soil and also measure the adsorption capacity of soils. Application of P to crop in the form of fertilizers can be adsorbed by the soil but may not be available for plants restricted with specific adaptations. Application of P containing fertilizers can increase available P in the soil hence increase crop yield which can be used to feed the world’s rapid population growth.
Keywords: Adsorption; mechanism of adsorption; phosphorus; phosphorus management intropical soil; phosphorus adsorption isotherm